(3OjhGf CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3djS HgG GdebOeI cGdfSNI GdSGHbI, hJHOC HGdTYQ eHGTQI(B: (3jG ehVY GdTOfjI GdhLfGA heUGQY GdEOdGL hGdESQGA s
(3BNQgG (B:s
(3ef bUjOI jGFjI(B: (3hCfj LOjQ Cf CNGa hCJbj hEf cfJ de CTQc HPj GdYQT KGfjG s
(3fSNI KGdKIs
(3hedMb HGdOjhGf bUjOI oJfSH ddEeGe GdTGaYj QVj Gddg Yfgs
(3HQhGjI GdUhdj hgj eQJHI Ydi GdehVhYGJ hJHOC HGdeOjMs
(3hQO CjVkG JMJ Qbe (B475(3, (B667(3, (B873(3, (B917(3, (B2202(3, (B3247 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
Keywords: (3GdCOHs